EXPLORING THE USE OF CHATBOT AS A MEDIA IN MOTIVATING THE STUDENTS TO LEARN SOLAR SYSTEM AND ENGLISH - Dhafa Alifandra; Suciana Wijirahayu; Indra Nurul Alam; Mentari Yuliani (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
The fact that teachers only rely on books as a learning aid for students is unfortunate, especially for elementary school students. They have high desire to explore and love to play with their imaginations. Therefore, an easy and practical technology is an alternative. Through a chatbot, educational materials comprising images, videos, and texts can motivate students in learning English. This study aimed to create a Chatbot AI Zeno to motivate the students in primary school to learn Solar System and English. The research method used in this study is the Research and Development method (R&D).The chatbot design is by the Rapid Application Development (RAD) method, to create the application fast and iteratively. The research subjects in this study were 30 grade 6 elementary school students at Tanjung Barat 04 Jakarta. Data collection techniques used questionnaires, interviews, documentation, and tests. The questionnaire consisted of questions about students' perceptions of chatbot design, about understanding of the material presented on Zeno the Solar System Patrol Man chatbot, and the students' perceptions about it. The results of the chatbot testing received positive responses from the teachers, and the students. Based on the evaluation, 90% of students reported feeling motivated and assisted in their learning while using the chatbot. Thus, the conclusion is that the Zeno chatbot can motivate and aid the learning process.